Analisis Pengaruh Budaya Kerja Berakhlak Terhadap Kinerja Pegawai Pada Sekretariat Daerah Kabupaten Tulungagung - Mustofa, Galaxy; Mutiara, Nisa (Universitas Islam Kadiri, 2026)
The public needs good governance. The challenges of governance today and in the future are much greater, so bureaucratic reform or changes in the system of government administration are needed. One effort to realize bureaucratic reform is through the concept of berakhlak work culture as a manifestation of basic values ​​that must be upheld by every ASN, especially for employees of the Regional Secretariat of Tulungagung Regency. Therefore, this study aims to analyze the influence of a berakhlak work culture on employee performance at the Regional Secretariat of Tulungagung Regency. The method used in this study is a descriptive quantitative method with a multiple linear equation model with SPSS statistical tools. The sampling technique uses purposive sampling with the Slovin formula so that a sample of 140 respondents is obtained. The data used is primary data measured by a Likert Scale through a questionnaire instrument distributed via Google Forms. The results of this study indicate that a berakhlak work culture has a significant positive effect on the performance of employees at the Regional Secretariat of Tulungagung Regency. In general, this indicates that the implementation of a berakhlak work culture with good morals is good enough to improve the performance of employees of the Regional Secretariat of Tulungagung Regency and implement a form of good governance.